Desarrollo de una aplicación pwa para la gestión de información de la Junta de Agua Regional Canchagua - Pilatasig Travez, Bryan Alexis (2022)
At the Canchagua Regional Water Board,there were problems in taking water readings due to the lack of technological tools that do not allow the reader to speed up the processing of the readings; the support used to enter information is usually done using sheets of paper. The form and the route assignments are done manually for the reader, so the information collected is sometimes inaccurate, in addition, the routes are not completely covered and the data digitalization is not real. For this reason it was proposed to develop a progressive web application (PWA) for the management of drinking water readings in order to optimize the time it takes to collect data from the meters and enter the readings provided by the water readers, having greater control of routes assigned to each reader, then used for the development of the project the methodology of agile practices,which facilitated the development of functionality through Sprints. As a result of the application was obtained the direct digitalization of readings and the generation of a PDF file of readings records, to complement it can be concluded that it was obtained the decrease of time in taking readings of the water meters of the different users, in turn allowing to obtain real data.